Profile of intrauterine fetal demise in Central India: is it preventable? - Patidar, Surbhi; Mahadik, Kalpana (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Intrauterine fetal demise (IUFD) refers to the death of a fetus after 20 weeks of gestation but before or during labor, and it remains a significant obstetric concern worldwide. This study investigates the profile of IUFD in Central India, focusing on its causes, associated maternal factors, and the potential for prevention. Globally, unexplained stillbirth is reported in 76% of cases. The study aims to find the causes of IUFD in this area to help in achieving the goal of less than 12 neonatal deaths. Methods: A retrospective observational study was conducted over two years from April 2022 to April 2024 at the Department of Obstetrics and Gynecology, R. D. Gardi Medical College, Ujjain, Madhya Pradesh. We included diagnosed cases of pregnancies with IUFD that presented at our hospital. Women before delivery and those who came in emergency with IUFD were included. Results: 151 cases of IUFD were diagnosed out of 4492 deliveries in the study period of two years; rate of 3.36%. The most common cause of IUFD was preeclampsia (24%) followed by unexplained causes (12%), obstructed and prolonged labor (9.9%). Inspite of tertiary care level of health facility most of these intrauterine deaths were not prevented due to poor antenatal care, late reporting and callous attitude of relatives. Conclusions: Certain causes of IUFD, such as congenital anomalies, are unavoidable, a significant proportion of cases could be prevented through enhanced maternal health management, improved prenatal screening, and better healthcare access across Central India.